2017
DOI: 10.1530/joe-17-0009
|View full text |Cite
|
Sign up to set email alerts
|

30 YEARS OF THE MINERALOCORTICOID RECEPTOR: The role of the mineralocorticoid receptor in the vasculature

Abstract: Since the mineralocorticoid receptor (MR) was cloned 30 years ago, it has become clear that MR is expressed in extra-renal tissues, including the cardiovascular system, where it is expressed on all cells of the vasculature. Understanding the role of MR in the vasculature has been of particular interest as clinical trials show that MR antagonism improves cardiovascular outcomes out of proportion to changes in blood pressure. The last 30 years of research have demonstrated that MR is a functional hormone-activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(46 citation statements)
references
References 114 publications
2
41
0
3
Order By: Relevance
“…Indeed, we show in the present study that depressed patients had higher glucose levels and lower HDL cholesterol values than healthy controls. Increased aldosterone is an established risk factor for mortality in CVD, and blocking MR has beneficial effects on many CVD endpoints, including mortality 69,70 . Several prospective studies in different populations have shown that higher cortisol values are associated with cardiovascular mortality [71][72][73] .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we show in the present study that depressed patients had higher glucose levels and lower HDL cholesterol values than healthy controls. Increased aldosterone is an established risk factor for mortality in CVD, and blocking MR has beneficial effects on many CVD endpoints, including mortality 69,70 . Several prospective studies in different populations have shown that higher cortisol values are associated with cardiovascular mortality [71][72][73] .…”
Section: Discussionmentioning
confidence: 99%
“…Mineralocorticoid receptor (MR) is a classic nuclear receptor and its antagonists have been used to treat patients with heart failure or resistant hypertension . MR in ECs has been shown to play important roles in cardiovascular homeostasis and pathogenesis . An endothelial MR‐deficient mouse has been created and used to demonstrate the importance of endothelial MR in the regulation of vascular dysfunction, remodeling, inflammation, and oxidative stress , as well as cardiac dysfunction, remodeling, inflammation, and oxidative stress .…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, MR is expressed in the heart [ 6 , 7 ], in all cell types of the vasculature, including smooth muscle cells (SMCs), endothelial cells (ECs) and fibroblasts, and has also been found in adipose tissue [ 8 ]. In this context, the MR has a relevant role in the control of cardiovascular and metabolic function [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%